Project 2-D Motion Simulation Based on Matlab Graphical User Interface in Physics Learning - Zulkarnain Zulkarnain; Islahudin Islahudin; M. Isnaini; Linda Sekar Utami; Khairil Anwar; Ni Wayan Sri Darmayanti (Universitas Muhammadiyah Purworejo, 2023)
Learning physics requires students to master the basic concepts of physics. Not infrequently, the physics concept is abstract, so it isn't easy to be perceived by students. However, abstract concepts in physics learning can be overcome by visualizing physics concepts packaged in computer software-based application programs in the form of computer simulations. This study aims to develop a 2-D motion simulation program based on the Matlab GUI. This study uses the Research & Development method. The development of this application program is carried out through 4 stages called 4-D: Define, Design, Develop, and Dissemination. The subjects in this study were 20 students of class XI MAS Nurul Jannah Ampenan. From the results of the study, it can be concluded that the quality of the product that has been developed is very feasible, with a percentage of 89,09% based on the assessment of material experts, 93,33% by media experts in the appropriate category, the response of students in class XI MAS Nurul Jannah Ampenan on the motion simulation application program 2- D-based GUI Matlab with a percentage of 88,20% with an excellent category, and an increase in understanding of physics concepts on the subject of 2-D motion; projectile motion after students use the 2-D motion simulation application program is in the medium category, seen from the class average gain value of 0.62. Therefore, the application program that has been developed has met the eligibility criteria and can be used in physics learning.